Transnational Nomads : How Somalis Cope with Refugee Life in the Dadaab Camps of Kenya. - Horst, Cindy (Forced migration., 2011)
There is a tendency to consider all refugees as 'vulnerable victims': an attitude reinforced by the stream of images depicting refugees living in abject conditions. This groundbreaking study of Somalis in a Kenyan refugee camp reveals the inadequacy of such assumptions by describing the rich personal and social histories that refugees bring with them to the camps. The author focuses on the ways in which Somalis are able to adapt their 'nomadic' heritage in order to cope with camp life; a heritage that includes a high degree of mobility and strong social networks that reach beyond the confine.